The Malay great works students' perception towards interface design elements Massive Open Online Course (MOOC) - Salmah Jan Noor Muhammad; N.S.A. Rahman; M.A.M. Aris; Asmiaty Amat (Advanced Research Trentz, 2020)
Technology learning, such as MOOC is necessary in modern society that ensures new knowledge and can be share. In teaching and learning, the use of MOOC will considered as a tool that can improve cognitive, psychomotor and affective to learners. MOOC, students can connect each other and free access that encourages borderless discussion. This study aims to identify issue and analyze student admissions to the MOOC design of BBK 4201 The Malay Great Works course. This study’s respondents involved 69 students of BBK 4201 The Malay Great Works at Universiti Putra Malaysia. This study’s emphasis will focus on the two main elements of design with the division of 8 items. Quantitative approaches will use to carry out this study. At the same time, the investigation will be using the Survey Monkey website and analyzed based on the Technology Acceptance Model (TAM) approach. This is because this approach will explicitly designed to analyze the technology acceptance. The study results show the level of tendency of students to be interested in MOOC design towards learning. The study results can also help give an overview to online course builders about face-to-face design that can increase student interest and understanding.